A large scale waterborne Campylobacteriosis outbreak, Havelock North, New Zealand. Issue 3 (September 2020) - Gilpin, Brent J.; Walker, Tiffany; Paine, Shevaun; Sherwood, Jill; Mackereth, Graham; Wood, Tim; Hambling, Tammy; Hewison, Chris; Brounts, Angela; Wilson, Maurice; Scholes, Paula; Robson, Beth; et al.
Highlights: Heavy rainfall caused drainage of sheep feces into a shallow aquifer. Consumption of untreated water resulted in up to 8320 campylobacteriosis illnesses. Genotyping of the Campylobacter helped define the source of the outbreak and cases. Safe drinking water requires a multibarrier approach. Abstract: Background: We describe the investigation of a Campylobacter outbreak linked to contamination of an untreated, groundwater derived drinking water supply. Methods: We analysed epidemiological data collected from clinician-confirmed diarrheal cases and estimated the total burden of Havelock North cases using an age-adjusted cross-sectional telephone survey. Campylobacter isolates from case fecal specimens, groundwater samples, and sheep fecal specimens from paddocks adjacent to the drinking water source were whole genome sequenced. Findings: We estimate between 6260 and 8320 cases of illness including up to 2230 who lived outside the reticulation area, were linked to the contaminated water supply. Of these, 953 cases were physician reported, 42 were hospitalized, three developed Guillain-Barré syndrome, and Campylobacter infection contributed to at least four deaths. Of the 12 genotypes observed in cases, four were also observed in water, three were also observed in sheep and one was also observed in both water and sheep. Interpretation: The contamination of the untreated reticulated water supply occurred following a very heavy rainfall event which caused drainage of sheep feces into a shallow aquifer. The existence of a routine clinical surveillance system for campylobacteriosis facilitated identification of the outbreak, recovery of clinical isolates, and early testing of the water for pathogens. Genotyping of the Campylobacter jejuni helped define the source of the outbreak and confirm outbreak periods and cases. Expected increases in heavy rainfall events and intensification of agriculture mean that additional safeguards are needed to protect populations from such drinking water outbreaks. Funding: NZ Ministry of Health, Health Research Council, ESR SSIF, Royal Society. Graphical abstract: Image, graphical abstract